2017
DOI: 10.1097/hjh.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Denervation of the distal renal arterial branches vs. conventional main renal artery treatment

Abstract: Percutaneous renal denervation treatment was significantly less effective at lowering 24-h blood pressure in treatment-resistant hypertensive patients when therapy was applied conventionally in the trunk of renal artery as compared with when applied to distal segmental branches. This observation is in accordance with previous surgical and anatomical findings showing that most renal nerve fibers are distant from the lumen proximally and become available for endovascular treatment mainly in the distal portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 18 publications
2
32
2
12
Order By: Relevance
“…Our overall BP effects are below the results of a recently published randomized trial by Pekarskiy et al . Compared with this trial, average baseline systolic BP on ABPM was lower in our trial cohort (153 mm Hg versus 170 mm Hg in the combined ablation groups), which is usually associated with a less pronounced BP drop following RDN .…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our overall BP effects are below the results of a recently published randomized trial by Pekarskiy et al . Compared with this trial, average baseline systolic BP on ABPM was lower in our trial cohort (153 mm Hg versus 170 mm Hg in the combined ablation groups), which is usually associated with a less pronounced BP drop following RDN .…”
Section: Discussioncontrasting
confidence: 97%
“…Importantly, renal function remained stable following the procedure, and no new renal artery stenoses were detected. This is in line with the results of 2 recent trials investigating renal artery branch ablation, where no alterations in duplex sonographic renal blood flow or catheter‐based renal angiogram (J. Davies, MD, unpublished data, presented at EuroPCR 2016) could be observed at follow‐up. However, long‐term safety of this optimized ablation approach clearly warrants further investigation in a larger prospective cohort.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, a recent anatomical study showed that the renal sympathetic nerve fibers are distributed closer to the lumen in branch renal arteries (RAs) compared with the main RA, suggesting that RDN that includes the branch RA may ablate more sympathetic nerves than RDN on the main RA alone . This hypothesis was supported in recent animal and clinical studies including the blinded, randomized, sham‐controlled SPYRAL HTN‐OFF MED and ON MED trials . Direct comparison studies in animals and humans clearly confirmed greater efficacy in RDN on both branch and main RA compared with RDN on main RA alone .…”
Section: Introductionmentioning
confidence: 74%
“…This hypothesis was supported in recent animal and clinical studies including the blinded, randomized, sham‐controlled SPYRAL HTN‐OFF MED and ON MED trials . Direct comparison studies in animals and humans clearly confirmed greater efficacy in RDN on both branch and main RA compared with RDN on main RA alone . Therefore, branch RA is expected to become the treatment site of choice for RF‐based RDN.…”
Section: Introductionmentioning
confidence: 76%